2017
DOI: 10.1186/s12889-017-4117-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk in a population of older adults with multiple co-morbidities in rural south africa: the HAALSI (Health and Aging in Africa: longitudinal studies of INDEPTH communities) study

Abstract: BackgroundA consequence of the widespread uptake of anti-retroviral therapy (ART) is that the older South African population will experience an increase in life expectancy, increasing their risk for cardiometabolic diseases (CMD), and its risk factors. The long-term interactions between HIV infection, treatment, and CMD remain to be elucidated in the African population. The HAALSI cohort was established to investigate the impact of these interactions on CMD morbidity and mortality among middle-aged and older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 36 publications
6
94
0
Order By: Relevance
“…In contrast to most studies from high-income countries (HIC), we found a lower prevalence of conventional CVD risk factors in the HIV-infected population on ART compared to the HIV-uninfected population [4]. These findings are in line with other publications on CVD risk in SSA [24,25]. The difference in CVD risk profile between the HIV-infected population in HIC and low-to middle-income countries (LMIC) most likely reflects the differences in the HIV epidemic between HIC and LMIC.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast to most studies from high-income countries (HIC), we found a lower prevalence of conventional CVD risk factors in the HIV-infected population on ART compared to the HIV-uninfected population [4]. These findings are in line with other publications on CVD risk in SSA [24,25]. The difference in CVD risk profile between the HIV-infected population in HIC and low-to middle-income countries (LMIC) most likely reflects the differences in the HIV epidemic between HIC and LMIC.…”
Section: Discussionsupporting
confidence: 85%
“…At baseline and at follow-up, however, the mean levels of hsCRP in HIV-negative women remained at average risk levels according to the Centers for Disease Control and Prevention and the American Heart Association [60]. Interestingly, women in a 2017 study of South Africans with a 22% prevalence of HIV infection had a high mean hsCRP concentration at baseline (3.3 mg/dL), which was also higher than the male mean baseline hsCRP concentration (3.1 mg/dL) [15]. HIV-positive women in our study had higher baseline values compared with HIV-negative women, consistent with other studies [21,56,61].…”
Section: Discussionmentioning
confidence: 99%
“…In PLWH, high-sensitivity C-reactive protein (hsCRP), D-dimer and transthyretin (prealbumin) have previously been examined as markers of inflammation. hsCRP is elevated in HIV-infected individuals compared with HIV-negative individuals, and independently predicts HIV-related mortality, HIV disease progression and risk for AIDS-and non-AIDS-related events [13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Higher D-dimer concentration in HIV infection has been associated with increased all-cause mortality and non-AIDS-related deaths [4,9,[29][30][31][32][33][34], although results may be inconsistent in women [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Participants in HAALSI were randomly sampled from the Agincourt Health and Demographic Surveillance Site (HDSS). Enrollment took place from November 2014 to November 2015 . The baseline survey was administered by local fieldworkers and participant responses recorded in a Computer‐Assisted Personal Interview system .…”
Section: Methodsmentioning
confidence: 99%